THE INFLUENCE OF STORE ATMOSPHERE, PRICE AND LOCATION OF THE PURCHASE OF THE CLOTHES IN THE THROOX STORE SOLO - Basuki Sri Rahayu; Oktavianus Aditia Saputra (STIE AUB Surakarta, 2019)
The purpose of this research is to find out and analyze the influence of store atmosphere, price and location to the purchasing decision on Throox store Solo. The population is the customers who come and purchase the clothing product on Throox store Solo and 100 people have been selected as samples. The data collection technique has been done by issuing questionnaires which is carried out after the validity test and the realibility test has been conducted. The data analysis technique is carried out by using classic assumption test (Normality test, Multicolinearity test, Heteroscedasticity test, autocoretalion test), multiple linear regression analysis, t test, F test and Multiple Determination Coefficient (R2). The results of this research showed that Multiple Linear regression test indicates that the price and the location of a positive effect, while the store atmosphere effect negatively to the purchase decision of the clothes in the Throox store Solo, t-test results showed that price and location are significant, influential, while store atmosphere does not influence on purchasing decisions in the clothing Throox store Solo, test results show that the factor F store atmosphere, the price and the location of significant effect simultaneously against the decision of the purchase of the clothes in the Throox store Solo, test Detrminasi Coefficient (R2) showed that store atmosphere, price and location of contributing 28.1% of purchase Throox clothes in the store.